O uso de ferramentas de tecnologia da informação e comunicação no desenvolvimento da pesquisa em Ciências Sociais: possibilidades e competências - Aleixina Maria Lopes Andalecio (2004)
Scientific research involves tasks that can be assisted by the use of tools of information and communication technologies. This work was developed with the objective of investigating when this assistance occurs and which abilities are necessary for the researchers so that they can make use of these tools. Towards this end, a bibliographical survey was made focusing on the evolution of information and communication technologies and their effect on contemporary society and InformationScience, the stages of the Social Sciences research, the use of tools of information and communication technologies in the several stages of the research and the abilities that contribute for them to be used effectively. A field work was also carried out in which participants of a doctoral program were interviewed to verify, in the daily routines of a certain group of researchers, how these tools are being used in their research work.The interviews allowed me to observe how these tools - mainly e-mail, text editing and Internet as source of information - are already considered indispensable, but many of them are still not adequately used.